Galur Isogenik Xanthomonas oryzae pv. oryzae Hasil Penyinaran Ultraviolet dan Potensinya Sebagai Penginduksi Resistensi Padi terhadap Penyakit Hawar Daun Bakteri - Yuliani, Fitria; Giyanto, Giyanto; Mutaqin, Kikin Hamzah (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2017)
Bacterial leaf blight (BLB) caused by Xanthomonas oryzae pv. oryzae is an important rice disease and may cause 50% plant damage. One approach to manage this disease is using isogenic non-pathogenic strain that can induce plant resistance. This study was conducted to obtain isogenic strains of X. oryzae pv. oryzae through ultraviolet irradiation and evaluate ability of the isolates in inducing plant resistance. Bacteria X. oryzae pv. oryzae were exposed to UV for 3, 5, 10 and 15 min. A total of 99 colonies obtained were selected through pathogenicity tests, followed by confirmation using XOR-F and XOR-R2 primers. As much as 16 isogenic strain isolates were obtained with the ability to produce exopolysaccharides (EPS) ranges between 1.4–9.8 mg mL-1 compared to wild-type 6.0 mg mL-1. Five isogenic strains isolates (M313, M57, M101, M1513 and M1515) caused virulence reduction of 92.8–98.6%. Application of those five isogenic isolates prolonged incubation period of X. oryzae pv. Oryzae, i.e. 6.6–5.4 days compared to the wild-type i.e. 4.8 days after inoculation. Suppression of disease progression was also observed with AUDPC value 615.0-827.5, which was lower than those caused by wild-type and control, i.e. 863.3 and 682.5, respectively. Application of isogenic strain isolates did not affect plant growth but it increased plant productivity. Isogenic strain M101 was the best isolate with an incubation period of 5.7 days after inoculation, having the lowest AUDPC value (615.0), and yielded dry weight of 100 grains higher (2.8 g) than those of the wild-type (2.0 g).